Vibration related white finger disease: a case report - Kurtul, Seher; Türk, Meral (The European Research Journal, 2019)
Vibration related white finger disease is frequently observed in workers exposed to hand-arm vibration. The main occupational exposure sources for hand-arm vibration are grinding, road and concrete breaking, using of grinding wheel, rotary saw, high pressure water hose, pneumatic hammer, drill, hammer, hand crusher, lawn mower, road roller. A 38-year-old male patient was admitted to our occupational disease clinic with complaints of pain on both fingertips, swelling on the fingers and occasional whitening of the fingers on both hands. There was a story of pneumatic hammer use in a private firm that produced heat resistant plate for 12 years and also work story in the same company for 2 years in the grinding department. The case was considered to be a white finger disease due to vibration with current findings and work history, and medical treatment for white finger disease was regulated. It has been suggested that the patient should do job change, work in a non-cold environment, and also avoid work that can cause vibration. This case who exposed hand-arm vibrations shows the importance of taking a detailed work history while taking an anamnesis. In screening the health effects of the hand-arm vibration, the complaints of white finger disease should be carefully questioned and examined. Vibration-related white finger disease, as in other occupational diseases, can be protected by taking effective measures at the workplace.